Make or buy: train in-company or recruit from the labour market? - Bellmann, Lutz [Verfasser]; Grunau, Philipp [Verfasser]; Troltsch, Klaus [Verfasser]; Walden, Günter [Verfasser] (My University, 2014)
"Using a sample about company hiring behaviour from the BIBB Establishment Panel on Training and Competence Development 2011, this paper analyses the hiring decisions of German establishments. Companies essentially have two choices to meet their labour demands: to provide their own apprenticeship training or to recruit unskilled or already-qualified staff through the external labour market. Therefore, we employ a multinomial quasi-maximum likelihood fractional regression model that simultaneously investigates the determinants of five hiring alternatives (new trainees, external unskilled staff, external skilled staff with initial vocational education, technicians and master craftsmen, and external staff with higher education). Our analysis reveals that a firm’s characteristics play a crucial role in explaining its recruitment behaviour. In this respect, the mobility and development of its workforce as well as the reproduction of the existing qualification structure prove especially important. The empirical results further show some evidence that apprenticeship training and the recruitment of workers with IVET qualifications from the external labour market depict alternative strategies." (Authors' abstract, BIBB-Doku)
Keywords: Arbeitskräftebedarf; Personalgewinnung; Betriebliche Berufsausbildung; BIBB-Qualifizierungspanel; Multivariate Analyse; Regressionsanalyse